The idea of a university - Newman, John Henry, Saint, 1801-1890 (Rethinking the Western tradition., 1996)
This edition of The idea of a University includes the full text of the original 1852 publication and four selections from the subsequently added "University Subjects" together with five essays by leading scholars that explore the background and the present-day relevance of Newman's themes